Analysis of abnormal epithelial lesions in cervical Pap smears in Mid-Western Nepal - SK Ranabhat; R Shrestha; M Tiwari (Association of Clinical Pathologists of Nepal, 2011)
Background: Like in other developing countries, cancer of cervix is one of the most common malignancies in women in Nepal. Most women never undergo a cervical Pap smear screening. The objective of this study is to determine the prevalence of abnormal cervical epithelial lesions. Materials and Methods: This was a retrospective study of 880 conventional cervical Pap smears reported from the Department of Pathology, Chitwan Medical College in Chitwan, Nepal. The time period was from June 2009 to November 2010. Results: In this study, High-grade Squamous Intraepithelial Lesion was the most common with 6 cases (40%), followed by Low-grade Squamous Intraepithelial Lesion with 3 cases (20%), then Atypical Squamous Epithelial Cells of Undetermined Significance, and atypical Glandular Cells and Squamous cell carcinoma with 2 cases each (13.3%). Eighty per cent of all the abnormal epithelial lesions were found in women above the age of 40 years. Conclusion: At least one Pap screening test of the cervix of all women between the ages of 40-50 years is recommended. Keywords: Pap smear; Cervical Intraepithelial Lesion; Squamous cell carcinoma. DOI: 10.3126/jpn.v1i1.4447 Journal of Pathology of Nepal (2011) Vol.1, 30-33